2015
DOI: 10.1016/j.biortech.2014.10.091
|View full text |Cite
|
Sign up to set email alerts
|

Improved azo dye decolorization in an advanced integrated system of bioelectrochemical module with surrounding electrode deployment and anaerobic sludge reactor

Abstract: h i g h l i g h t sIntegrated system with BES module and ASR was developed for azo dye treatment. It improved decolorization and electrochemical performance without co-substrate. COD can be removed after cleavage of the azo bond, different from biocathode BES. Cooperation of cathode, biofilm, and sludge played an important role in treatment. t r a c tA new integrated system, embedding a modular bioelectrochemical system (BES) with surrounding electrode deployment into an anaerobic sludge reactor (ASR), was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…The lower resistance gave rise to a higher current, would eventually facilitate the electron transfer and reduce the running cost. Importantly, one group electrodes took up 15.0% of the reactor volume, much lower compared with the other reported application-oriented BESs, including the up-flow biocatalyzed electrolysis reactor (UFBER) (28%) (Cui et al, 2012) or the modified integrated BES system (55.7%) (Kong et al, 2015). Additionally, the horizontal type configuration avoided the extra costs brought by the global gravity, like some up-flow type BES (Cui et al, 2012), is more suitable to deal with large amount of wastewater in the sewage treatment plant or as the simulation for in situ bioelectrochemical remediation of river water body.…”
Section: Discussionmentioning
confidence: 87%
“…The lower resistance gave rise to a higher current, would eventually facilitate the electron transfer and reduce the running cost. Importantly, one group electrodes took up 15.0% of the reactor volume, much lower compared with the other reported application-oriented BESs, including the up-flow biocatalyzed electrolysis reactor (UFBER) (28%) (Cui et al, 2012) or the modified integrated BES system (55.7%) (Kong et al, 2015). Additionally, the horizontal type configuration avoided the extra costs brought by the global gravity, like some up-flow type BES (Cui et al, 2012), is more suitable to deal with large amount of wastewater in the sewage treatment plant or as the simulation for in situ bioelectrochemical remediation of river water body.…”
Section: Discussionmentioning
confidence: 87%
“…It would be a great potential application for industry feasibility, especially with BES module embedding into the traditional anaerobic sludge reactor. It has been found that the performance of azo dye wastewater treatment can be significantly improved by embedding the BES module with surrounding electrode deployment into anaerobic sludge reactor (ASR) to form integrated BES-ASR in the treatment process (Kong et al, 2015). This integrated process not only allowed electrons produced from wastewater at anode to be an electron donor for removing pollution at cathode, but also realized some organics removal through the anaerobic process of the sludge, implying good synergy between these two technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The BES-ASR integrated reactor was developed by inserting sleeve-type BES module (inner tube full of holes: ID 3 cm  H 10 cm) into an anaerobic sludge reactor (ASR: outer tube ID 8 cm  H 10 cm), as previously described with the anaerobic sludge at the bottom (Kong et al, 2015). Carbon brush anode was placed in the center of the inner tube, surrounding the carbon brush cathode in the outer tube with the electrode ratio of 1:3.…”
Section: Configuration Of the Integrated Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…. Its advantages have been demonstrated in some cases, for example desalination, decolorization and the treatment of chromium (Huang et al, 2010;Jacobson et al, 2011;Kong et al, 2015bKong et al, , 2015c. These studies indeed provided the feasibility of the BES with sleeve-type configuration to treat wastewater, however, as a sustainable and environment-friendly technology, the practical application of BES is strongly limited by their configuration optimum and the assembled optimization for operation (Ge et al, 2014;Gil-Carrera et al, 2011;Ping and He, 2013;Raman and Lan, 2012;Uría et al, 2012), which could provide important theory for further scale-up.…”
Section: Introductionmentioning
confidence: 99%